Thermoelectric Device «ALTEC-7012» for Human Head Cooling - Anatychuk, L.I.; Knyshov, G.V.; Krykunov, О.А; Kobyliansky, R.R.; Tyumentsev, V.A.; Moskalyk, І.А. (Science and Innovation, 2024)
The results of computer simulation of thermophysical processes in the human head at given heat fluxes on its surface have been presented. The disadvantages of the existing physical models of the human head have been established and the ways for their improvement have been proposed. A prototype ALTEC-7012 thermoelectric device for cooling the human head has been designed and manufactured. The device is promising for human brain hypothermia.